METHODOLOGY OF FULLY MASTERING THE BASICS OF MATH ANALYSIS (Web of Teachers: Inderscience Research, 2025)
In this article, cadets study the technology of constructing mathematical concepts using the example of the process of constructing mathematical concepts.